Biodegradation of plastics from waste electrical and electronic equipment by greater wax moth larvae (Galleria mellonella). (10th August 2021) - Zhu, Ping; Pan, Xusheng; Li, Xiaowei; Liu, Xiankai; Liu, Qiang; Zhou, John; Dai, Xiaohu; Qian, Guangren
Abstract: Disposal of the increasing amount of the plastics from waste electrical and electronic equipment (WEEE) is of great concern. In this study, biodegradation feasibility of waste rigid polyurethane (WRPU), waste polystyrene (WPS) and waste acrylonitrile-butadiene-styrene (WABS) from WEEE by Galleria mellonella larvae were investigated. The cumulative consumptions of WRPU, WPS and WABS are 35.08%, 13.41% and 4.87% of the total 2 g plastic within 7 d, respectively. TG-MS shows a decrease in the total weight loss and the changes of weight loss stages, implying that thermal stabilities of the three plastics drop. Meanwhile, Mn and Mw of the WPS and WABS decrease after the digestion, suggesting the depolymerization and biodegradation of the plastics. Fluorescence imaging demonstrates that total fluorescence intensity of the WRPU has a considerable decrease from 5.904 × 10 9 to 5.140 × 10 9 after digestion by Galleria mellonella larvae for 24 h. High-throughput sequencing reveals that the relative abundance of Enterococcus in the WABS and WPS groups increases and Enterobacter decreases, while WRPU shows the opposite trend. The findings suggest active adaptability of intestinal microbes to WEEE plastics with different properties, indicate the feasibility of Galleria mellonella larvae biodegrading the WEEE plastics, and provide a new potential biological treatment for WEEE plastics. Graphical abstract: Image 1 Highlights: Galleria mellonella had great chewing ability to WRPU, WPS and WABS plastics. TG-MS and GPC analysis confirmed biodegradation of the three WEEE plastics. Fluorescence imaging was used to track the fate of WRPU in Galleria mellonella . Intestinal microbes had active adaptability to degrade WEEE plastics with different properties.